Perubahan Beberapa Sifat Kimia Tanah Podsolik Merah Kuning dengan Pemberian Kompos serta Pengaruhnya terhadap Produksi Tanaman Caisim (Brassica juncea L.) - Elesta Banamtuan; Maria Imelda Humoen; Desak Ketut Tri Martini; Ade Irma Sulistiani; Ermenia Pereira Dos Santos; Natalia Desy Djata Ndua (Savana Cendana, 2023)
The main problem faced in the utilization of Red Yellow Podsolic soil (RYP) is the low nutrient content and poor physical and chemical properties of the soil. Problems with the chemical properties of RYP soil include acidic soil pH, low organic C content, low available P, low CEC and low interchangeable bases (K, Ca, Mg, Na). This study aims to improve some of the chemical properties of PMK soil with the application of compost as an ameliorant and its effect on the growth and yield of caisim (Brassica juncea L.) as an indicator plant. The study used a single factor Completely Randomized Design (CRD) with 5 treatments consisting of no compost (K0), compost 5 tons/ha (K5), compost 10 tons/ha (K10), compost 15 tons/ha (K15) and compost 20 tons/ha (K20). The results showed that the application of compost at a dose of 20 tons/ha (K20) was able to increase the pH, C-Organic, CEC, available of P and exch-Ca, exch-Mg, exch-K and exch-Na of RYP soil and increase the production of caisim.